Predictors of social media use among international students in Klang valley, Malaysia : gratifications sought, beliefs and attitudes towards social media - Higazi, Abdalla Ibrahim Yousif (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
Social media, as an online phenomenon, have developed rapidly and dramatically changing the way people communicate and interact globally. Social media, such as Facebook, MySpace and Twitter not only attract users but have caught the attention of scholars and researchers to explore how people use these websites and the gratifications sought and gratifications obtained from them. The main objective of the present study is to investigate how international students (IS) use social media and the gratifications they seek and obtain from using them. This study examines the effect of beliefs, attitudes and gratifications sought (GS) on social media use (SMU). Finally, the study explores the impact of social media use (SMU) on gratifications obtained (GO). The Uses and Gratifications Theory (U&GT) was used as a theoretical framework to guide this research. The study utilized a cross-sectional design to elicit data from international students (IS) in Klang Valley, Malaysia. From 340 questionnaires administered to international students (IS), the findings indicate that all respondents are social media users who spend around one hour daily on social media. The majority of the respondents were males, Muslims and have more than 100 friends in their profiles. The results of the analysis reveal that international students (IS) use social media for five motives: education, religious information, entertainment, social interaction and communication motives and these motives were identified as the most salient factors of gratifications obtained (GO). The findings of the study show strong relationship between gratifications sought (GS) and gratifications obtained (GO). The results indicate that all respondents were satisfied with their usage of social media. The results of the analysis reveal that belief had a direct effect on attitude and gratifications sought (GS) and indirect influence on social media use (SMU) and gratifications obtained (GO) through attitude factor. While attitude had a direct significant impact on social media use (SMU), gratifications sought (GS) did not. Finally, social media use (SMU) had direct influence on gratifications obtained (GO) and mediated the relationship between attitudes and gratifications obtained (GO) on one side and mediated the relationship between beliefs and gratifications obtained (GO) on the other.